Sensitive but Sane: Male Visionaries and their Emotional Display in Interwar Belgium - Van Osselaer, Tine (BMGN - Low Countries Historical Review, 2012)
When a wave of Marian apparitions swept over Belgium in 1932-1935 many ‘visionaries’ (c. 200), among them a remarkably high number of men, claimed to encounter the divine. Focusing on these male visionaries and their emotional expressivity, this article aims not only at contributing to a better understanding of Catholic constructions of masculinity, it also accords with the increased attention for the historicity of emotions and, more specifically, for men’s emotional comportment. The male visionaries present a particularly interesting case since they had to live up to multiple expectations about their emotions. Whereas their visibility and trustworthiness as visionaries were founded on their capacity to display their emotions (in accordance with a tradition of emotional mysticism), these men also had to show ‘masculine’ rationality and coolness in order to prove that their experiences were not triggered by exaggerated piety or neurosis. This article is part of the special issue 'Low Countries Histories of Masculinity'.